The Effect of Self Assessment System and Tax Knowledge on Individual Taxpayer Compliance - WIBOWO, Ahrizlia Sahidevi; KARAMOY, Herman; LAMBEY, Robert (PT Keberlanjutan Strategis Indonesia, 2022)
Taxes are people's contributions to the state treasury which are used to support the work program of the government to implement changes, so that government goals can be achieved. The role of the taxation sector is very large in supporting state revenues, so that in this case the awareness of the public as corporate taxpayers and personal taxpayers is really needed. The self-assessment system is one of the government's efforts in growing individual tax revenues by giving confidence to taxpayers to be active in carrying out their own tax obligations. In implementing the self-assessment system, taxpayers need to understand tax knowledge. Tax knowledge is a basis that can support the implementation of the current system. This study aims to determine the effect of self-assessment system and tax knowledge on individual taxpayer compliance. The research population is taxpayers domiciled in the city of Manado with a sample of 100 respondents. The research method uses questionnaires and analytical techniques using multiple linear analysis assisted by the SPSS Version 25 application program. The results of the study show that the self-assessment system variable does not have a significant effect on individual taxpayer compliance, while the tax knowledge variable has an influence on individual taxpayer compliance.